Comparison of Continuous Epidural Blockade and Continuous Femoral Nerve Block on Postoperative Pain in Total Knee Replacement Surgeries: A Prospective Randomised Controlled Study - K. Shanthini; Nishkala Chandra Sekar; Kusuma Mathai (Academia Anesthesiologica International, 2020)
Background: The use of epidural analgesia in the management of postoperative pain following orthopedic surgeries has evolved as a critical component of a multimodal approach to achieve the goal of pain relief, early mobilization, and improved compliance with physiotherapy resulting in overall improved outcomes. Aim: The aim of this study is to compare continuous femoral nerve block with continuous epidural block technique for postoperative analgesia in patients undergoing elective total knee replacement surgery.Subjects and Methods:The patients belonging to the ASA I to III scheduled for various knee surgeries under spinal anesthesia were enrolled in this study. They were randomly divided into two equal groups of thirty-three patients each. The Group F patients received continuous femoral nerve blockade and in the Group E patients continuous epidural blocked preoperatively.Results:The analgesic efficacy of both continuous femoral nerve block and continuous epidural nerve block was equal as measured by the visual analogue scores. The incidence of Hypotension was more in the Epidural group. The adverse effects due to the Continuous Femoral Nerve block were lower in comparison with the Continuous Epidural block technique.Conclusion:Continuous femoral nerve blockade provides postoperative analgesia equivalent to that obtained with a continuous epidural blocked but with lesser side effects.